Kinerja Kelembagaan, Relasi Struktural, dan Koalisi Advokasi Pemerintah Daerah: Studi kasus Pengentasan Kemiskinan di Kabupaten Malang - Yunita, Primadiana; Pohan, Ibnu Asqori; Syauki, Wifka Rahma (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
This research analyzes poverty alleviation by the Malang Regency Government through a collaborative governance approach or collaborative governance. The Malang Regency is contributing to East Java's high rate of poverty. In this report, qualitative techniques are applied. In the process of obtaining appropriate data and information, interviews and documentation are techniques implemented. It found that there are no legal provisions in the aspect of institutional arrangements in the form of any provisions that explicitly state the elements of poverty reduction collaboration but in the strategic aspects and concepts of poverty alleviation written in the 5th Malang Regency Mission as well as in the RPJMD 2016-2021. In addition, in the context of structural relationships, it shows that only horizontally across OPDs does the pattern of interaction and connectivity of collaboration to minimize the level of poverty in Malang Regency. Finally, there is no coalition in the Malang Regency created to alleviate poverty in coalition advocacy.